Cost effectiveness of clinical associates: A case study for the Mpumalanga province in South Africa - Joris Hamm; Petra van Bodegraven; Martin Bac; Jakobus M. Louw (AOSIS, 2016)
Background: The National Department of Health of South Africa decided to start a programme to train mid-level healthcare workers, called clinical associates, as one of the measures to increase healthcare workers at district level in rural areas. Unfortunately, very little is known about the cost effectiveness of clinical associates. Aims: To determine, on a provincial level, the cost effectiveness of training and employing clinical associates and medical practitioners compared to the standard strategy of training and employing only more medical practitioners.Methods: A literature study was performed to answer several sub questions regarding the costs and effectiveness of clinical associates. The results were used to present a case study. Results: The total cost for a province to pay for the full training of a clinical associate is R 300 850. The average employment cost per year is R196 329 and for medical practitioners these costs are R 730 985 and R 559 397, respectively. Effectiveness: Clinical associates are likely to free up the time of a medical practitioner by 50-76%. They can provide the same quality of care as higher level workers, provided that they receive adequate training, support and supervision. Furthermore, they seem more willing to work in rural areas compared to medical practitioners. Conclusions: The case study showed that training and employing clinical associates is potentially a cost-effective strategy for a province to meet the increasing demand for rural healthcare workers. This strategy will only succeed when clinical associates receive adequate training, support and supervision and if the province keeps investing in them.